2021
DOI: 10.3389/fcimb.2021.700323
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Clinical Trial: Oral Miltefosine and Pentavalent Antimonials Associated With Pentoxifylline for the Treatment of American Tegumentary Leishmaniasis

Abstract: IntroductionAmerican tegumentary leishmaniasis (ATL), which can present as either cutaneous (CL) or mucosal leishmaniasis (ML), is endemic in South America, and first-line antimonial treatments are known for their wide range of adverse effects (AEs). Growing reports of drug resistance increase the urgency of the need for better treatment options. The objective of this pilot clinical trial was to assess the efficacy of and AEs associated with the oral combination of miltefosine and pentoxifylline based on a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…However, efficacy rates are lower in the presence of ML, particularly in the “mucosal belt” of Peru, Bolivia, Paraguay, and southern Brazil, where ML is highly endemic. On average, the treatment failure rate is endorsed at around 40% in these highly endemic regions [ 9 , 11 ]. Miltefosine has demonstrated effective cure rates in ML caused by the Vianna subgenus in Brazil, Bolivia, Ecuador, and Argentina, with cure rates upwards of 70% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, efficacy rates are lower in the presence of ML, particularly in the “mucosal belt” of Peru, Bolivia, Paraguay, and southern Brazil, where ML is highly endemic. On average, the treatment failure rate is endorsed at around 40% in these highly endemic regions [ 9 , 11 ]. Miltefosine has demonstrated effective cure rates in ML caused by the Vianna subgenus in Brazil, Bolivia, Ecuador, and Argentina, with cure rates upwards of 70% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This trial found no statistically significant difference between the two medications’ curative potential. However, a statistically significant increase in unwanted side effects from the sodium stibogluconate treatment was present, which may result in more frequent interruptions in treatment and subsequent prolongation of treatment duration [ 11 ]. Cochrane review of systemic therapies for cutaneous and mucocutaneous leishmaniasis concluded that meglumine antimoniate and miltefosine were the most likely systemic medications to have increased rates of cure, but that evidence was mostly low to moderate in quality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations were tested using Pearson’s r. Bootstrapping method was used to resample data and test correlation between cytokine levels and clinical parameters. Effect sizes of the differences between groups were calculated in the pilot clinical trial ( Martins et al., 2021 ). Using IBM ® SPSS Statistics, we calculated one-way multivariate analysis of variance (MANOVA) to compare age and group effects in the pilot clinical trial, and effect size r of Mann–Whitney was used to compare various quantitative variables at the end of the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Dr. in Therapeutic Innovation Institution: Federal University of Northern Tocantins (UFNT) 2 Graduating in Medicine Institution: Federal University of Northern Tocantins (UFNT) 3 Graduating in Medicine Institution: Federal University of Northern Tocantins (UFNT) 4 Undergraduate student in Medicine 5 Undergraduate student in Medicine Institution: Centro Universitário Tocantinense Presidente Antônio Carlos (UNITPAC), Afya 6 Graduating in Medicine Institution: Centro Universitário dos Guararapes (UNIFG) 7 Graduating in Medicine Institution: Federal University of Northern Tocantins (UFNT) 8 Undergraduate student in Medicine Institution: Federal University of Northern Tocantins (UFNT) 9 Undergraduate student in Medicine Institution: Faculty of Higher Education of Amazônia Reunida (FESAR) 10 Post-Graduate in Systems Engineering Institution: Federal University of Northern Tocantins (UFNT) 11 Undergraduate student in Medicine Institution: Federal University of Northern Tocantins (UFNT)…”
mentioning
confidence: 99%